Psoriasis is the independent factor for early atherosclerosis: A prospective study of cardiometabolic risk profile - Dinić, Miroslav Ž.; Zečević, Radoš D; Hajduković, Zoran; Mijušković, Mirjana; Đurić, Predrag; Jović, Zoran; Grdinić, Aleksandra; Petrović, Mirjana; Terzić, Brankica; Pejović, Janko; Kandolf Sekulović, Lidija (Vojnosanitetski pregled, 2017)
Background/Aim. Psoriasis as multisystemic inflammatory disease is related with an increased cardiometabolic risk. The aim of the study was to analyze risk biomarkers, peripheral and renal arteries ultrasonography and echocardiography for subclinical atherosclerosis and metabolic disease in 106 subjects (66 psoriasis patients and 40 controls, 20 eczema patients and 20 healthy volunteers). Methods. In all exameenes following parameters were analyzed: body mass index (BMI), C-reactive protein, D-dimer, serum amyloid A (SAA), apolipoprotein (Apo) A1, ApoB, ApoB/Apo A1 index, fasting glucose, C-peptide, fasting insulinemia, homeostatic model assessment-insulin resistance (HOMA-IR), HOMA-β-cell, lipid profile, serum uric acid concentration (SUAC), 24-h proteinuria and microalbuminuria. Carotid, brachial, femoral and renal arteries ultrasonography, as well as echocardiography was also performed. Results. Five of 66 (7.6%) psoriasis patients had metabolic syndrome (not present in both control groups). The following variables were increased in patients with psoriasis compared to both control groups: BMI (p = 0.012), insulinemia (p < 0.001), HOMA-IR (p = 0.003), HOMA-β cell (p < 0.001), SUAC (p = 0.006), ApoB/ApoA1 ratio (p = 0.006) and microalbuminuria (p < 0.001). Also, increased C-peptide (p = 0.034), D-dimer (p = 0.029), triglycerides (p = 0.044), SAA (p = 0.005) and decreased ApoA1 (p = 0.014) were found in the psoriasis patients compared to healthy controls. HDL cholesterol was decreased in the psoriasis patients compared to the control group of eczema patients (p = 0.004). Common carotid (CIMT) and femoral artery intima-media thickness (FIMT) was significantly greater (p < 0.001) and the maximal flow speed (cm/s) in brachial artery significantly decreased (p = 0.017) in the patients with psoriasis in comparison to both control groups. In multivariate logistic regression analysis, after the adjustment for confounding variables, the most important predictor of CIMT and FIMT was the diagnosis of psoriasis (p < 0.001). Conclusion. Cardiometabolic risk biomarkers and ultrasonographic signs of early atherosclerosis are correlated with the diagnosis of psoriasis, and not to generalized eczema. Psoriasis was found to be an independent risk factor for subclinical atherosclerosis.